Romanies within the interlocking matrix of racialization: How Ciganos in Brazil became accused of introducing an infectious disease - MARTIN FOTTA (Romani Studies)
Brazilian medical texts sometimes forge a link between Ciganos (Romanies) and the spread of trachoma, an infectious eye disease. The form of the claim has become standardized into something like this: trachoma was brought to the country in the eighteenth century by Ciganos who were deported from Portugal to the provinces of Maranhão and Ceará. This article traces the origins of this claim to a group of early twentieth-century ophthalmologists from Northeast Brazil, particularly in Ceará. It reveals that several racial projects are folded into the claim and makes a case for the need to approach the dynamics of racialization of Romanies relationally. The analysis of the Romani societal position, characteristics ascribed to them in relation to other communities, and the ways those communities are racialized not only reveals new insights but breaches the continued insularity of Romani studies. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.